ДИФФЕРЕНЦИРОВАННОЕ КОМПЛЕКСНОЕ ЛЕЧЕНИЕ ПАЦИЕНТОВ, СТРАДАЮЩИХ БОЛЕЗНЬЮ ПАРКИНСОНА, С УЧЁТОМ СТЕПЕНИ АТРОФИЧЕСКИХ ИЗМЕНЕНИЙ ВЕЩЕСТВА ГОЛОВНОГО МОЗГА - V. A. Chipizubov (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The objective of this study was to compare the results of complex (medicinal and surgical), and only medicinal treatment of patients with rapidly progressive and dyskinesia associated forms of Parkinson's disease. Three atrophy indices (IA) of the brain matter were proposed to justify a differentiated approach to the treatment of each form. Multivariable regression analysis showed, that patients, who were treated with complex method and had IA-1 less than 0.16, IA-2 - less than 0.115, IA-3 - less than 0.06, had the best improvement of the clinical status during the follow-up period. There were also multiple correlation coefficients obtained in the range 0.911-0.943, which indicates a significant linear relationship between the factors of influence (IA) and response (clinical presentation). In groups with only conservative treatment, the coefficients were in the range of 0.331-0, 423, indicating low and medium dependence on clinical manifestations of atrophy indexes. The status of all patients was assessed after 3, 6, 12 and 18 months. It turned out that in case of the earlier mentioned indices values the result of the treatment was constant during the entire period of observation. It was statistically confirmed by the assessment of the squares of the Mahalanobis distance.